2015
DOI: 10.4049/jimmunol.1402924
|View full text |Cite
|
Sign up to set email alerts
|

DC-SCRIPT Regulates IL-10 Production in Human Dendritic Cells by Modulating NF-κBp65 Activation

Abstract: The balance between tolerance and immunity is important for the outcome of an infection or cancer, and dendritic cells (DCs) are key regulators of this balance. DC-specific transcript (DC-SCRIPT) is a protein expressed by DCs and has been demonstrated to suppress both TLR-mediated expression of IL-10 and glucocorticoid receptor–mediated transcription of glucocorticoid-induced leucine zipper (GILZ). Because GILZ is known to promote IL-10 production, we investigated whether these two processes are linked. Dual-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
6
18
0
Order By: Relevance
“…In this study, GK treatment inhibited the expression of p-NF-κB/p65 and upregulated the Nrf2 pathway, indicating potential complicated crosstalk between NF-κB and Nrf2, which may contribute to the improvement in the inflammatory microenvironment of the brain and promote neuroprotection and nerve regeneration. In this study, the inhibition of NF-κB and TNF-α in OGD astrocytes treated with GK might be related to the increased expression of IL-10 ( 41 43 ). Additionally, a series of studies have demonstrated that the activation and nuclear translocation of Nrf2 and the expression of various antioxidant enzymes can be mediated via the PI3K/Akt pathway ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 63%
“…In this study, GK treatment inhibited the expression of p-NF-κB/p65 and upregulated the Nrf2 pathway, indicating potential complicated crosstalk between NF-κB and Nrf2, which may contribute to the improvement in the inflammatory microenvironment of the brain and promote neuroprotection and nerve regeneration. In this study, the inhibition of NF-κB and TNF-α in OGD astrocytes treated with GK might be related to the increased expression of IL-10 ( 41 43 ). Additionally, a series of studies have demonstrated that the activation and nuclear translocation of Nrf2 and the expression of various antioxidant enzymes can be mediated via the PI3K/Akt pathway ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 63%
“…GO analysis identified significant enrichment in functions related to OC biology, ( Supplementary Figure S2B , right) and HOMER analysis revealed putative TF binding motifs such as Jun/Fos, BATF or ZNF528 ( Supplementary Figure S2C ). These small 5mC changes across cell differentiation affected genes involved in proteolytic activity ( CTSK, ADAMTS8, HYAL2 ) and related with NF-κB regulation ( URGCP and WDFY1 as activators and ZNF366, SLC39A1 and CUX1 as inhibitors) ( 35 37 ). Bisulfite pyrosequencing of representative CpGs ( CTSK and ZNF366 ) confirmed their demethylation in OCs, but also some partial demethylation in MACs ( Supplementary Figure S2D ), suggesting that the observed differences may be indirect rather than the result of specific targeting by elements downstream of RANKL.…”
Section: Resultsmentioning
confidence: 99%
“…Since activation of tolDCs has been shown to increase lymph node homing, antigen presentation, and stability against other inflammatory modulators ( 32 ), we activated Dex-treated DCs with MPLA (DM-DCs), a non-toxic clinical grade analog of LPS, which also signals via toll-like receptor 4 and exhibits potent immune-stimulatory capacity ( 33 , 34 ). Glucocorticoid receptors are transcription factors that suppress the pro-inflammatory program induced by TLRs and in turn potentiate TLR-mediated anti-inflammatory responses such as IL-10 secretion ( 35 , 36 ). Our group has previously shown that Dex and MPLA induce a tolerogenic profile in moDCs from both healthy controls and RA patients ( 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%